ANALISIS PASAR TENAGA KERJA SEKTOR INDUSTRI TERHADAP TINGKAT UPAH DI INDONESIA - Yulia Putri; Mike Triani (Universitas Negeri Padang, 2019)
This study aims to to know and to analyze influence ( 1 ) the number of labor in the industrial sector in indonesia on wage levels in indonesia .( 2 ) working hours in the industrial sector in indonesia on wage levels in indonesia .( 3 ) together the amount of labor and working hours in the industrial sector in indonesia on wage levels in indonesia .Type research, this research is descriptive where data used is secondary data in cross section or of the year 2017 and related institutions.In this research using a technique of analysis a linear regression berganda to find how free variable influence on variables bound.The research results obtained show that: ( 1 ) the number of workers on the industrial sector in indonesia influential positive and insignificant on wage levels in indonesia.( 2 ) working hours on the industrial sector in indonesia positive and significant influence on wage levels in indonesia.In bersama-sama numbers of workers and working hours on the industrial sector in indonesia significant impact on wage rates in indonesia with the level of influence 41 %.So it can from the research suggested that the importance of the role of manpower and the government to cooperate in improving the wage rates in indonesia.